Analisis Struktur dan Nilai Pendidikan dalam Novel Dalingding Angin Janari Karya Usep Romli H.M - RIZKI NURFAUZI; Fahmi Rakhman (Prodi Pendidikan Bahasa dan Sastra Daerah, 2023)
This study aims to: 1) analyze the structure of the novel Dalingding Angin Janari by Usép Romli H.M; 2) as well as analyzing the educational value in the novel Dalingding Angin Janari by Usép Romli H.M. This research is a qualitative research and the method used is descriptive analysis method. The technique for collecting data used literature study techniques and the data source in this study was the novel Dalingding Angin Janari by Usép Romli H.M. The results of this study are: 1) the novel Dalingding Angin Janari by Usép Romli H.M has a theme about family problems, the plot is a mixture of bobok tengah plots and backward plots (mixed plot), there are 41 actors involved consisting of 1 main actor, namely Nendah, 2 the second actor, namely Fenny and her mother and 38 additional actors and has 20 place settings, 50 time settings and 2 atmosphere settings; 2) in the novel Dalingding Angin Janari by Usép Romli H.M there are 56 educational attitudes divided into religious attitudes (21), honesty (1), tolerance (1), discipline (1), hard work (4), creative (2), independent (0), democracy (0), curiosity (1), love of the motherland (1), national spirit (1), respect for achievements (5), communication / friendship (5), fond of reading / studying (5), caring for the environment (2), social care (2), responsibility (2) and peace-loving (2).